Tax evasion behavior using finite automata: Experiments in Chile and Italy - Garrido, Nicolás; Mittone, Luigi (Expert systems with applications, 2012)
► In this study we model the tax evasion behavior of subjects in experiments run in Chile and Italy. ► The behavior is captured using a Moore Automata with a Binary Stochastic Output Function. ► We show that low complexity automata capture most of the 70% of subject behavior. In this paper, we use a Moore Automata with Binary Stochastic Output Function in order to capture the extensive decision regarding tax evasion made by subjects in experiments run in Chile and Italy. Firstly, we show how an hypothesis about subject behavior is converted into an automaton, and how we compute the probabilities of evading for every state of an automaton. We use this procedure in order to look for the automaton which is able to anticipate the highest number of decisions made by the subjects during the experiments. Finally, we show that automata with few states perform better than automata with many states, and that the bomb-crater effect described in Mittone (2006) is a well identified pattern of behavior in a subset of subjects.